The influence of obesity on folate status, DNA methylation and cancer-related gene expression in normal breast tissues from premenopausal women - Armina-Lyn M. Frederick; Chi Guo; Ann Meyer; Liying Yan; Sallie S. Schneider; Zhenhua Liu (Epigenetics, 2021)
Epidemiological studies have established obesity as a critical risk factor for postmenopausal breast cancer (post-BC), whereas a reverse association holds prior to menopause. A significant scientific gap exists in understanding the mechanism(s) underpinning this epidemiological phenomenon, particularly the reverse association between obesity and premenopausal breast cancer (pre-BC). This study aimed to understand how folate metabolism and DNA methylation inform the association between obesity and pre-BC. Fifty normal breast tissue samples were collected from premenopausal women who underwent reduction mammoplasty. We modified the Lactobacillus Casei microbiological folate assay and measured folate levels in our breast tissue samples. The DNA methylation of LINE-1, a biomarker of genome-wide methylation, and the expression of a panel of breast cancer-related genes was measured by pyrosequencing and real-time PCR. We found that a high BMI is associated with an increase of folate levels in mammary tissue, with an increase of 2.65 ng/g of folate per every 5-unit increase of BMI (p < 0.05). LINE-1 DNA methylation was significantly associated with BMI (p < 0.05), and marginally associated with folate concentration (p = 0.087). A high expression of SFRP1 was observed in subjects with high BMI or high folate status (p < 0.05). This study demonstrated that, in premenopausal women, obesity is associated with increased mammary folate status, genome-wide DNA methylation and SFRP1 gene expression. Our findings indicated that the improved folate and epigenetic status represents a novel mechanism responsible for the reverse association between obesity and pre-BC.